Analisis dan Desain Sistem Informasi Berbasis Website Gereja Katolik Santo Yusup Jember - Rizky Basatha; Boniface Boliona Badilangoe Keraf (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2022)
An organization or community institution consists of a group of people who work together for the purposes or interests of their organization or institution. . Paroki Santo Yusup Jember is a community institution located on Jalan R.A. Kartini 28, Jember. As a community institution that requires an integrated information needed for all their activities, both about displaying information, registering, processing the required data in a practical and efficient manner. With the creation of this information system, all information and all registrations will be greatly assisted and facilitate the work of the Church secretariat effectively and precisely in the future. Therefore, a journal was created for the Analysis and Design of Website-Based Information Systems for Gereja Katolik Santo Yusup Jember. It is hoped that the existence of this information system can help in the effectiveness and efficiency of activities around the church.